PENGARUH DOMINASI METODE CERAMAH TERHADAP KEJENUHAN BELAJAR SISWA KELAS 11 DI SMAN 1 PERCUT SEI TUAN - Nazwa Aulia; Samuel Revaldo Jeverseon Siboro; Nurul Mardiah; Olive Katrina Joyanka Sihombing; Bona Pintura Suyana Pandiangan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The dominance of conventional lecture-based instruction in class XI of SMAN 1 Percut Sei Tuan was identified as the primary determinant of learning boredom among students, establishing the central focus of this investigation. This uniform instructional approach progressively diminished student activeness, intensified academic disengagement, and degraded both attentional capacity and motivational orientation. Accordingly, this study was designed to analyze the relationship between lecture method hegemony and cognitive fatigue while assessing the relative effectiveness of diversified instructional strategies. Through a descriptive qualitative framework, participatory observation and documentation served as primary instruments for examining pedagogical patterns, classroom atmosphere, and students' behavioral responses. Empirical results demonstrated that lecture-dominated instruction produced measurable learning boredom, characterized by minimal constructive participation, deteriorating attentiveness, and disruptive manifestations including drowsiness and contextually irrelevant conversation. This condition shifted markedly when interactive pedagogical elements were introduced through questioning techniques, structured peer discussion, and contextualization of subject matter within students' experiential realities. These findings collectively affirm that instructional approaches embracing variety, interactivity, and innovation represent a pedagogically superior alternative, demonstrating greater capacity to cultivate meaningful student engagement and sustain intrinsic learning motivation than lecture-centered conventional instruction.